Mathematical modelling for the transmission dynamics of Rift Valley fever virus with human host - Oguntolu, Festus Abiodun; Yavalah, Deborah W.; Udom, Collins F.; Peter, Olumuyiwa James; Oshinubi, Kayode (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
Rift Valley Fever (RVF) is a viral zoonosis spread primarily by mosquitos that primarily affects livestock but has the potential to affect humans. Because of its potential to spread quickly and become an epidemic, it has become a public concern. In this article, the transmission dynamics of RVF with mosquito, livestock and human host using a compartmental model is studied and analyzed. The basic reproduction number R0 is computed using next generation matrix and the disease-free equilibrium state is found to be locally asymptotically stable if R0 1 which implies that rift valley fever could be put under control in a population where the reproduction number is less than 1. The numerical simulations give insightful results to further explore the dynamics of the disease based on the effect of three interventions; efficacy of vaccination, culling of livestock and trapping of mosquitoes introduced in the model.